Pengabdian Kepada Masyarakat : Peningkatan Pemahaman Nilai Islam di TPQ Nurul Hikmah melalui Lomba Cerdas - Muhammad Saiful Hidayat; Alisa Chusuma Dewi; Shifa Divanti; Atika Rohmah (ALKHIDMAH: Jurnal Pengabdian dan Kemitraan Masyarakat, 2024)
This community service is designed to complement and enrich religious learning at TPQ Nurul Hikmah. The purpose of implementing this community service is to help female students at the Nurul Hikmah Al-Qur'an Education Park (TPQ) better understand and assimilate Islamic beliefs. This activity aims to assess students' understanding of Islamic teachings while fostering a competitive and enjoyable learning environment through the LCC competition. This service has a significant role because it can answer problems that occur related to the lack of understanding of Islamic values ​​among TPQ participants. The competition material is specifically designed to discuss various Islamic concepts that focus on the five daily prayers and emulating the characteristics of the Prophet Muhammad SAW. The results of the activity showed an increase in interest in reading the Qur'an and hadith as well as a growing understanding of the importance of living according to Islamic principles. This service resulted in positive values ​​in female students who were more enthusiastic in understanding Islamic values ​​due to the methods used in delivering the material.